The Influence of Learning Video Media On Protocol Health Knowledge Covid-19 Elementary School Students - Pipit Festi Wiliyanarti; Nurma Yuliyanasari; Badruli Martati (Universitas STRADA Indonesia, 2021)
High Prevalence covid 19 school-age children to be a problem throughout the world, including Indonesia. Increasing children's knowledge through learning media is expected to be easily accepted so that the implementation of protocols can be implemented by child. The purpose of this study was to analyze the effect of instructional video media on the knowledge of Covid health protocol. This is a pre- experimental study, useda static group comparison design approach. Sampleof study consisted of the treatment groups are primary school age children are 24 people, the group that did not receive treatment as many as 30 children by purposive sampling. Analysts use in dependent T test, α=0.05. There was an effect of instructional video media on the knowledge of covid health protocol for 19 elementary school students with a sig result of 0.00. Learning using video media can increase the knowledge of elementary school students in implementing health protocols.